Educational pathways in a German labor market knowledge graph - Kostadinovska, Katerina [Verfasser]; Dörpinghaus, Jens [Verfasser] (My University, 2024)
„Educational pathways play a pivotal role in fostering lifelong learning and skilled workforces. We build upon a German labor market knowledge graph that was developed from the German Labor Market Ontology (GLMO). The GLMO provides entities for qualifications, such as occupations and training programs, as well as tools and skills. To conduct research on educational pathways, we employ several graph algorithms, such as shortest paths, and present the results. It is possible to demonstrate the advantages of digital methods in sociological research, thereby advancing the boundaries of computational social sciences in labor market research.“ (authors‘ abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; 370; Arbeitsmarktforschung; Datenanalyse; Bildungsverlauf